Design, Synthesis, Pharmacodynamic and In Silico Pharmacokinetic Evaluation of Some Novel Biginelli-Derived Pyrimidines and Fused Pyrimidines as Calcium Channel Blockers - Ahmed M. Farghaly; Ola H. Rizk; Inas Darwish; Manal Hamza; Mezna Saleh Altowyan; Assem Barakat; Mohamed Teleb (Molecules, 2022)
Some new pyrimidine derivatives comprising arylsulfonylhydrazino, ethoxycarbonylhydrazino, thiocarbamoylhydrazino and substituted hydrazone and thiosemicarbazide functionalities were prepared from Biginelli-derived pyrimidine precursors. Heterocyclic ring systems such as pyrazole, pyrazolidinedione, thiazoline and thiazolidinone ring systems were also incorporated into the designed pyrimidine core. Furthermore, fused triazolopyrimidine and pyrimidotriazine ring systems were prepared. The synthesized compounds were evaluated for their calcium channel blocking activity as potential hypotensive agents. Compounds 2, 3a, 3b, 4, 11 and 13 showed the highest ex vivo calcium channel blocking activities compared with the reference drug nifedipine. Compounds 2 and 11 were selected for further biological evaluation. They revealed good hypotensive activities following intravenous administration in dogs. Furthermore, 2 and 11 displayed drug-like in silico ADME parameters. A ligand-based pharmacophore model was developed to provide adequate information about the binding mode of the newly synthesized active compounds 2, 3a, 3b, 4, 11 and 13. This may also serve as a reliable basis for designing new active pyrimidine-based calcium channel blockers.